Continuous Monitoring Using a Wearable Device Detects Activity‐Induced Heart Rate Changes After Administration of Amphetamine. Issue 6 (27th September 2019) - Izmailova, Elena S.; McLean, Ian L.; Hather, Greg; Merberg, David; Homsy, Jason; Cantor, Matthew; Volfson, Dmitri; Bhatia, Gaurav; Perakslis, Eric D.; Benko, Christopher; Wagner, John A.
Abstract : Wearable digital devices offer potential advantages over traditional methods for the collection of health‐related information, including continuous collection of dense data while study subjects are ambulatory or in remote settings. We assessed the utility of collecting continuous actigraphy and cardiac monitoring by deploying two US Food and Drug Administration (FDA) 510(k)‐cleared devices in a phase I clinical trial of a novel compound, which included the use of an amphetamine challenge. The Phillips Actiwatch Spectrum Pro ( Actiwatch ) was used to assess mobility and sleep. The Preventice BodyGuardian ( BodyGuardian ) was used for monitoring heart rate (HR) and respiratory rate (RR), via single‐lead electrocardiogram (ECG) recordings, together with physical activity. We measured data collection rates, compared device readouts with conventional measures, and monitored changes in HR measures during the amphetamine challenge. Completeness of data collection was good for the Actiwatch (96%) and lower for the BodyGuardian (80%). A good correlation was observed between device and in‐clinic measures for HR ( r  = 0.99; P  < 0.001), but was poor for RR ( r  = 0.39; P  = 0.004). Manual reviews of selected ECG strips corresponding to HR measures below, within, and above the normal range were consistent with BodyGuardian measurements. The BodyGuardian device detected clear HR responses after amphetamine administration while subjects were physically active, whereas conventional measures collected at predefined timepoints while subjects were resting and supine did not. Wearable digital technology shows promise for monitoring human subjects for physiologic changes and pharmacologic responses, although fit‐for‐purpose evaluation and validation continues to be important prior to the wider deployment of these devices.